Maker music: Incorporating the maker and hacker community into music technology education. Issue 3 (1st December 2018) - Hughes, Alayna
Music Production and Technology education has traditionally concentrated on audio engineering, studio recording techniques with the focus of preparing students for a career as a producer or engineer. While necessary to retain the fundamentals of audio and recording, music technology education could do a service to students by including topics from the maker community by encouraging technology innovation. While some topics such as synthesis, programming and electronics are taught in graduate programmes, these are still seen as 'specialty' topics and students in undergraduate programmes miss out on learning other technologies and career paths that could benefit them. I would argue that by not updating the topics in music technology education that this has contributed to the stale output of the music industry within changing times. By incorporating topics such as microcontrollers, interaction and programming, students could discover new ways to work with music and learn skills that will give them more career opportunities. This article will discuss the ideals of the maker and music hacking movement, current pedagogy in Music Production and Technology degree programmes in the United States and United Kingdom and European Union, and the advantages of merging invention and DIY education into the current music technology and music production pedagogy.